Penerapan Asas Kelangsungan Usaha Pasca Pembatalan Homologasi Perjanjian Perdamaian dalam PKPU Berdasarkan Undang-Undang Kepailitan dan PKPU - Sabina Rezqita Dwi Cahya; Deviana Yuanitasari; Pupung Faisal (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
value of the bankruptcy estate (boedel pailit) through the going concern principle. Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (UUK-PKPU) allows curators to continue the debtor’s business, particularly under Article 179 paragraph (1). However, the absence of clear normative parameters creates legal uncertainty and inconsistent practices. This study analyzes the application of the going concern principle in the settlement of bankruptcy estates following the annulment of homologated composition agreements and examines the urgency of technical implementing regulations. Using a normative juridical method supported by statutory analysis, court decisions, legal doctrines, and interviews, the research focuses on the cases of PT Sri Rejeki Isman Tbk. (Sritex) and PT Texmaco Perkasa Engineering Tbk. The findings reveal that going concern implementation depends not only on legal provisions but also on non-legal factors, such as transparency, asset control, capital availability, management credibility, and creditor support. Texmaco’s case shows approval when these conditions are met, while Sritex demonstrates rejection due to lack of transparency and unlawful activities. The study underscores the need for a Supreme Court Regulation (PERMA) that establishes eligibility parameters, approval mechanisms, reporting obligations, and curator protection to ensure consistency, legal certainty, creditor protection, and greater economic benefits in Indonesian bankruptcy practice.